Cam design: analysis of kinetic and kinematics of cams profile / Abdul Razak Jafar and Mohd Kamal Shahrum - Jafar, Abdul Razak; Shahrum, Mohd Kamal (1994)
Cams are used widely in variety of machine, such as packaging machines, can-making machinery, engines, mechanical and electronics computers, wire-forming machines and computers mechanics. One important reason why cam are preferred over other types element is that the use of cams makes it possible to obtain an unlimited variety of motion and when certain basic requirements are followed, cams perform satisfactory year after year. For this project, we are analysed the kinetic and kinematics aspects of cams profile. The definition of kinetic is an element of physics that deals with the effects of forces that cause motion in mechanisms. The kinematics is the study of mechanisms without references to the forces that cause the movement. The most important thing in cams design, is the analysis of cam motion, analysis for combination of cam motion, to determine the cam profile - analytical method, determines pressure angle and reaction of cam when certain value of forces to apply in certain area of surface cam. In cam motion, we analysed all motion who are involved in combination of cam motion in one cycle revolution - 360 degrees.